Perfil cognitivo, capacidade funcional e tempo de reação simples em idosos: um estudo comparativo e correlacional - Santos Júnior, Raimundo Borges dos (Universidade Federal do Tocantins, 2023)
Objective: To verify the correlation between functional capacity, reaction time, and cognition, as well as to compare the variables among different age groups in older adults. Materials and Methods: The study had a cross-sectional, correlational, and comparative nature. Older adults over 60 years of age of both sexes participated in the study. The groups were organized according to age ranges of "60 to 70 years" and "above 70 years." The participants underwent assessments of: Cognition, Functional Capacity - using the tests "Chair Stand" (CS), "Forearm Flexion" (FF), "2.44m Walk and Sit" (WWS), "Reach Behind Back" (RBB), "Sit and Reach" (SR), "6-Minute Walk" (6MW), and Simple Reaction Time. Results: A positive and significant association was found in women between functional capacity variables (FF x CS; r = 0.636; p<0.001) and inverse associations between variables (WWS x CS; r = -0.488; p<0.01) and (WWS x FF; r = - 0.390; p<0.05). In men, an inverse and significant association was found only in the variables (WWS x FF; r = -0.857; p<0.05). Women in the age range of 60 to 70 years showed better performance in cognition (25.47 ± 2.06 vs. 23.08 ± 4.33 points; p<0.05). Conclusions: No significant associations were found between cognition and reaction time in older adults. The levels of cognition in women showed differences, indicating that age appears to have an impact on this variable. Future research that expands the geographical and population scope is recommended.